2007
DOI: 10.1124/jpet.107.122994
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Human Breast Cancer Resistance Protein (BCRP/ABCG2) in Lipid Rafts/Caveolae and Modulation of Its Activity by Cholesterol in Vitro

Abstract: Breast cancer resistance protein (BCRP/ABCG2) is an active efflux pump that belongs to the ATP-binding cassette (ABC) transporter family. It is located in various tissues involved in drug absorption, distribution, and elimination and plays an important role in multidrug resistance. For P-glycoprotein, another member of the ABC transporter family, it is well established that it is at least partly located in cholesterol and sphingolipid-enriched domains of the plasma membrane called "lipid rafts" and that the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 39 publications
(42 reference statements)
3
91
0
Order By: Relevance
“…ABCG2 was found in Triton X-100-insoluble lipid rafts in close interaction with cholesterol and caveolin (Storch et al, 2007). As discussed below, in the case of ABCG2, cholesterol is an essential modulator of the transport activity; thus, raft localization may be advantageous for its proper functioning.…”
Section: P0130mentioning
confidence: 98%
See 2 more Smart Citations
“…ABCG2 was found in Triton X-100-insoluble lipid rafts in close interaction with cholesterol and caveolin (Storch et al, 2007). As discussed below, in the case of ABCG2, cholesterol is an essential modulator of the transport activity; thus, raft localization may be advantageous for its proper functioning.…”
Section: P0130mentioning
confidence: 98%
“…Both ABCB1 and ABCG2 have been reported to reside in detergentinsoluble rafts (Ismair et al, 2009;Orlowski, Martin, & Escargueil, 2006;Radeva, Perabo, & Sharom, 2005;Storch, Ehehalt, Haefeli, & Weiss, 2007) and in close interaction with cholesterol and caveolin. In the canalicular membranes of hepatocytes, several ABC transporters, including ABCB4 (MDR3), ABCB11 (BSEP, S-P-gp), ABCC2 (MRP2), and ABCG5/G8, have also been shown to reside in raft domains (Ismair et al, 2009).…”
Section: P0095mentioning
confidence: 99%
See 1 more Smart Citation
“…Cholesterol and Hyaluronan Synthesis-Cholesterol is an important component of the plasma membrane, enriched in the heterogenous and dynamic lipid raft microdomains that have been suggested to regulate the function of multiple plasma membrane proteins (51,52). We have previously shown that overexpressed GFP-HAS3 is partly colocalized in lipid rafts and that M␤CD removes the hyaluronan synthesis-induced microvilli, a site for active hyaluronan synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Caveolin-1 function in this context has been linked to another ABC transporter, the BCRP protein, since it was shown that Caveolin-1 co-distributes with BCRP in detergent-resistant membrane fractions and interacts there with BCRP [142,148]. Interestingly, in Caveolin-1 knock-down cells, BCRP activity was reduced and the cells became more sensitive to mitoxantrone-induced reduction in cell proliferation [142].…”
Section: Mechanisms Of Caveolin-1-mediated Drug Resistancementioning
confidence: 99%